National Geographic dawn to dark photographs : the magic of light - Susan Tyler Hitchcock (National Geographic, 2013)
"The latest entry in National Geographic's popular photo line gives readers a front-row seat to the wonders of landscape photography. Choosing from among the world's best portfolios, curators at National Geographic have arranged a symphony of photographs that tell the story of a single day, from dawn's first light to the closing moments of sunset, from daylight to dark. Short legends accompany every photograph to explain the picture, the scene it conveys, or how the photographer captured it, along with quotations from literature that provide historical context. With the widest possible array of perspectives, close-ups, and details, these photos present a lifetime of vision, each page a new experience of time and light"--